Refleksi Nilai-Nilai Pancasila Dalam Praktik Pendidikan Karakter Pada Mahasiswa - Koebanu, Dunosel; Saingo, Yakobus Adi (DAS Institute, 2024)
This research aims to discuss the reflection of Pancasila values ​​in the practice of Character education for postgraduate students of the Master of Christian Religious Education, Kupang State Christian Institute. This research uses the literature research method where data is collected from various scientific literature, such as reference books, proceeding articles, scientific journals, and so on, to be summarized and analyzed reductively to explain the results of implementing and reflecting Pancasila values ​​in educational practice. Characteristics of Masters students at the Kupang State Christian Institute (IAKN Kupang) are felt to have significant and meaningful benefits because they can create a conducive campus life and unite. The contribution of Pancasila values ​​in the practice of character education makes every student more aware of establishing harmonious friendships with each other in the campus environment and avoiding various forms of discriminatory attitudes. Although it is acknowledged that there are still individual students who sometimes violate cultural norms and show negative character, every teaching staff member always strives to help these individual students change their behavior to become more Indonesian people who live the values ​​of Pancasila.